Dielectric Spectroscopy and Thermal Properties of Poly(lactic) Acid Reinforced with Carbon-Based Particles: Experimental Study and Design Theory - Spinelli, Giovanni (Polymers (Basel), 2020)
In the present study, polylactic acid (PLA) enriched with carbonaceous particles like multi-walled carbon nanotubes (MWCNTs), graphene nanoplates (GNPs) or a combination of both up 12 wt % of loading are used for producing 3D-printed specimens with fused deposition modeling (FDM) technology which are then experimentally and theoretically investigated. The goal is to propose a non-conventional filaments indicated for additive manufacturing process with improved dielectric and thermal properties, compared to the performances exhibited by the unfilled polymer. In the light of the above, a wide dielectric spectroscopy and a thermal analysis, supported by a morphological investigation, are performed. The results highlight that the introduction of 1-dimensional filler (MWCNTs) are more suitable for improving the dielectric properties of the resulting materials, due to the enhancement of the interfacial polarization and the presence of functionalized groups, whereas 2-dimensional nanoparticles (GNPs) better favor the thermal conduction mechanisms thanks to the lower thermal boundary resistance between the two phases, polymer/filler. In particular, with a loading of 12 wt % of MWCNTs the relative permittivity reaches the value of 5.35 × 10(3) much greater than that of 3.7 measured for unfilled PLA while for the thermal conductivity the enhancement with 12 wt % of GNPs is about 261% respect the thermal behavior of the neat polymer. The experimental results are correlated to theoretical findings, whereas a design of experiment (DoE) approach is adopted for investigating how the different fillers influence the dielectric and thermal performances of the 3D-printed parts, thus assisting the design of such innovative materials that appear promising for development and applications in the electromagnetic (EM) field and heat transfer.